2020
DOI: 10.1002/acn3.51078
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal biomarkers in amyotrophic lateral sclerosis

Abstract: after first publication: footnote 'a' has been inserted beside the authors Fen Huang and Yuda Zhu as they've equally contributed to this article.]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
84
1
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 80 publications
(96 citation statements)
references
References 41 publications
4
84
1
5
Order By: Relevance
“…While longitudinal studies on CSF NfL concentrations in ALS would be best suited to support this observation, these are scarce and mostly comprise small numbers of patients. Some longitudinal studies reported rather stable levels throughout the disease course ( Benatar et al, 2018 ; Huang et al, 2020 ), but slightly decreasing ( Steinacker et al, 2016 ) and increasing concentrations in specific subpopulations of ALS patients ( Lu et al, 2015 ; Poesen et al, 2017 ; Skillbäck et al, 2017 ) have been reported as well.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…While longitudinal studies on CSF NfL concentrations in ALS would be best suited to support this observation, these are scarce and mostly comprise small numbers of patients. Some longitudinal studies reported rather stable levels throughout the disease course ( Benatar et al, 2018 ; Huang et al, 2020 ), but slightly decreasing ( Steinacker et al, 2016 ) and increasing concentrations in specific subpopulations of ALS patients ( Lu et al, 2015 ; Poesen et al, 2017 ; Skillbäck et al, 2017 ) have been reported as well.…”
Section: Discussionmentioning
confidence: 96%
“…Most of these studies calculated the decline in ALSFRS-R from symptom onset until CSF sampling ( Tortelli et al, 2012 ; Lu et al, 2015 ; Menke et al, 2015 ; Steinacker et al, 2016 , 2018b ; Poesen et al, 2017 ; Andres-Benito et al, 2018 ; Gong et al, 2018 ; Scarafino et al, 2018 ; Schreiber et al, 2018 ) or from symptom onset until disease diagnosis ( Gaiani et al, 2017 ; Rossi et al, 2018 ). However, linear mixed-effects models using consecutively obtained ALSFRS-R scores have also been used to demonstrate associations with CSF NfL levels ( Huang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neurofilament light chain (Nf-L), a structural protein of the neuronal cytoskeleton, is a reliable biomarker of axonal injury and neurodegeneration. Nf-L is elevated in the CSF and blood of patients across neurodegenerative diseases including Alzheimer’s disease, amyotrophic lateral sclerosis [ 20 ], and multiple sclerosis (MS) [ 21 , 22 , 23 ]. In addition, CSF and blood Nf-L levels have been shown to be responsive to disease-modifying treatment in relapsing forms of MS [ 24 ], spinal muscular atrophy [ 25 ], and lysosomal storage disorders such as neuronal ceroid lipofuscinosis type 2 (CLN2) [ 26 ], suggesting it is possible to monitor treatment effects on neurodegeneration in peripheral biofluids.…”
Section: Introductionmentioning
confidence: 99%
“…Steps to consider when selecting biomarkers for use in early phase clinical trials include defining the scientific questions that the biomarker should help answer, performing a thorough literature review to select fit-forpurpose biomarker, bioanalytical method development or assay and laboratory selection, analytical model validation testing, and defining the clinical sampling, data reduction and analysis strategy [191,196]. Preferably the selected biomarkers are validated in the preclinical models used during drug development as well as in patients or patient biofluid repositories [197]. Characteristics to select a useful biomarker include that the biomarker should give a consistent response across studies and drugs with the same mode of action, must respond clearly to therapeutic doses, must have a clear dose-response relationship and ideally there should be a plausible relationship between the biomarker, pharmacology of the drug class, and disease pathophysiology (although for mechanistic biomarkers, this not an absolute necessity as discussed previously) [25].…”
Section: Biomarker Selection Development and Validationmentioning
confidence: 99%